Reoxygenation of Asphyxiated Newborn Piglets: Administration of 100% Oxygen Causes Significantly Higher Apoptosis in Cortical Neurons, as Compared to 21%. (25th March 2014) - Faa, G.; Fanos, V.; Fanni, D.; Gerosa, C.; Faa, A.; Fraschini, M.; Pais, M. E.; Di Felice, E.; Papalois, A.; Varsami, M.; Xanthos, T.; Iacovidou, N.
Abstract : Objective . Evaluation of neuronal changes in an animal experimental model of normocapnic hypoxia- reoxygenation. Materials and Methods . Fifty male piglets were the study subjects; normocapnic hypoxia was induced in 40 piglets and ten were sham-operated (controls). When bradycardia and/or severe hypotension occurred, reoxygenation was initiated. Animals were allocated in 4 groups according to the oxygen concentration, they were resuscitated with 18%, 21%, 40%, and 100% O2 . Persisting asystole despite 10 minutes of cardiopulmonary resuscitation and return of spontaneous circulation were the endpoints of the experiment. Surviving animals were euthanized and brain cortex samples were collected, hematoxylin and eosin-stained, and examined for apoptotic bodies observing 10 consecutive high power fields. Results . Histological examination of the control group did not show any pathological change. On the contrary, apoptosis of neurons was found in 87.5% of treated animals. When specimens were examined according to the oxygen concentration used for resuscitation, we found marked intergroup variability; a higher percentage of apoptotic neurons was observed in piglets of group 4 (100% oxygen) compared to the others (P = 0.001 ). Conclusions . This preliminary data shows that normocapnic hypoxia and reoxygenation in Landrace/Large White piglets resulted in significant histological changes in the brain cortex. The degree of pathological changes in cortical neurons was significantly associated with the oxygen concentration used for reoxygenation, with a higher percentage of apoptotic neurons being observed in piglets reoxygenated with 100% compared to 18% O2 and to 21% O2 .